Boron vs. Phosphorus in granitic pegmatites: The Cap de Creus case (Catalonia, Spain) - Alfonso,P.; Melgarejo,J.C. (Journal of the Czech Geological Society, 2000)
Four granitic pegmatite types are distinguished in the metapelite-hosted Cap de Creus pegmatite field: barren microcline-rich pegmatites (type I), beryl-columbite subtype pegmatites (type II), beryl-columbite-phosphate subtype pegmatites (type III) and albite type pegmatites (type IV). The abundance of tourmaline is inversely proportional to that of the phosphates: it is widespread in all the internal zones of the P-poor type I and II pegmatites, becomes very rare in the P-rich type III pegmatites and it is absent in the type IV. Nevertheless, tourmalinization is developed in the exocontacts of all the pegmatite types. All of the tourmaline crystals in the pegmatites and exocontacts belong to the schorl-dravite and schorl-foitite series, although Li phosphates are essential components in the most evolved pegmatites. In the less evolved, P-poor pegmatites, tourmaline crystallization, as well as that of other ferromagnesian silicates, depletes the concentration of Mg and Fe in the magma, and Fe/(Fe+Mg) in tourmalines increases during the course of crystallization of the pegmatite. Meanwhile, in the most evolved P-rich pegmatites, Fe-Al-Li-Mg phosphates are formed instead of silicates, boron is fractionated with excess phosphorus into the residual fluids, and tourmaline and apatite are formed by metasomatism of the host rock
Keywords: Tourmaline; electron microprobe; phosphorus; boron; granitic pegmatite